Pola Asuh dan Kejadian Stunting Pada Keluarga Tidak Mampu di Kelurahan Salo Kabupaten Pinrang - Wahyuni, Sinar; Haniarti, Haniarti; Wahyuni Sari, Rasidah (Jurnal Ilmiah Manusia Dan Kesehatan, 2026)
Stunting remains a major public health problem in Indonesia, including Pinrang Regency, with consequences for children’s physical growth, cognitive development, and future productivity. Its causes are not only linked to economic limitations but also closely related to parenting practices. Some poor families have successfully prevented stunting through positive caregiving practices, making the Positive Deviance (PD) approach relevant to explore. This study aimed to identify parenting patterns among low-income families in Salo Village and their relationship to stunting in children aged 6–59 months. A qualitative method with a phenomenological approach was employed. The study involved 10 informants, consisting of mothers of stunted and non-stunted children, posyandu cadres, and health workers. Data were collected through in-depth interviews, observation, and anthropometric measurements, then analyzed using data reduction, data presentation, and conclusion drawing. The findings showed that families with stunted children generally provided monotonous food with limited variety, were inconsistent in exclusive breastfeeding, and rarely utilized health services. In contrast, poor families with non-stunted children practiced PD, including exclusive breastfeeding, preparing simple but nutritious meals, maintaining household and environmental hygiene, and regularly attending posyandu. The study concludes that parenting practices are a key determinant in preventing stunting, even under economic constraints. The Positive Deviance approach offers an effective strategy for community empowerment by identifying and applying local solutions based on available resources.